REFLECTION ON THE NATIONAL ARCHITECTURAL IDENTITY OF MALAYSIA: A QUALITATIVE STUDY BASED ON THE THOUGHTS OF ACHMAD MOERDIJAT - Asif, Nayeem; Mohd Zuki, Muhammad Zulhilmi; Hussain, Muhammad Haikal; Mohamad Fouzi, Muhammad Aliff Zharfan; Ardiansyah, Ridho (Journal of Architecture, Planning and Construction Management, 2020)
This paper aims to document the finding on the national architecture identity of Malaysia based on the thoughts of renowned architect Achmad Moerdijat. Malaysian architecture today is a synthesis of architectural languages in which many are strongly influenced by western ideas, ranging from the Neo-Classical to the International Style and Post Modernism. The primary issue concerning Malaysian architecture is that Many architects today realized Malaysia lacks an identity if its own in terms of architecture. The lack of discourses, research, and documentation on Malaysian architectural identity are among the factors that contributed to a persistent misunderstanding of architecture identity and its association with the political, economic, and socio-cultural context of Malaysia. Ar. Ir. Achmad Moerdijat was selected to gain more insight into this issue considering his attachment period and architectural practice in the Malaysian context to find out his philosophy and principle in design and further upon his opinion of the subject matter of national architecture identity of Malaysia. The research proceeded through an exclusive interviewing session with the architect, where he shared his opinion on National Architectural in Malaysia. The findings showed that Malaysia is still in search of the architectural identity itself. This is due to the lack of research in terms of culture in Malaysia by the architects. The next issue is that the client only looks forward to the aesthetics looks rather than implying the National Architectural Malaysia style in the design. The aesthetics looks will increase the demands of profit, but the value of our architectural style is not there. Further research on this topic is recommended to gain a holistic view of the issue of the national architectural identity of Malaysia.